Layered security for IEEE 1687 using a Bimodal Physically Unclonable Function - Randa, Maulana; Bozdal, Mehmet; Samie, Mohammad; Jennions, Ian K. (Elsevier, 2018)
In this paper, a layered security mechanism for IEEE 1687 is proposed using a new class of physically unclonable function (PUF) called Bimodal PUF. It moves beyond the conventional single-challenge single-response PUF by introducing a second response to the PUF gained from the same single challenge. As an advantage, a double-response PUF forms two-layer security solution, one at the hardware layer by limiting the access to the embedded instrument and the second one for the data layer by securing the output data that needs to be transmitted. Experiments conducted with FPGA show that such advantages come in place at a small silicon area overhead, up to 1.4%, for a 64-bit security key. This is known to be sufficient enough to resist brute-force and machine learning attack.
Keywords: IJTAG; IEEE 1687; physically unclonable function; linear-feedback shift register; encryption